The mDCF combination as first-line therapy in patients with locally advanced or metastatic esophageal squamous cell carcinoma - V. V. Sokolovskiy; E. A. Dinaeva; A. A. Margusheva; A. A. Tryakin (Malignant tumours, 2026)
Introduction. There is no consensus regarding the optimal first-line chemotherapy regimen for locally advanced or metastatic esophageal squamous cell carcinoma. The efficacy of standard chemotherapy combinations is limited and therefore has to be improved. Due to the limited accessibility of modern immunotherapy, chemotherapy remains a valuable commonly used option. We conducted a non-randomized prospective study to evaluate the efficacy and tolerability of the triple combination mDCF. Materials and Methods. The main inclusion criteria of the study were locally advanced or metastatic esophageal squamous cell carcinoma, age over 18 years, patients with an ECOG performance status of ≤ 2 (ECOG, Eastern Cooperative Oncology Group), and satisfactory blood test results. The primary endpoint of the study was the objective response rate (ORR); secondary endpoints included overall survival (OS) and progression-free survival (PFS). Patients received eight cycles of mDCF chemotherapy: docetaxel 40 mg / m2 on day 1, cisplatin 40 mg / m2 on day 1, calcium folinate 400 mg / m2 also on day 1, fluorouracil 400 mg / m2 by intravenous bolus on day 1, followed by a 48-hour infusion of fluorouracil 2000 mg / m2 (1000 mg / m2 daily) on days 1–2. This treatment regimen was administered every 2 weeks. Results. From 2019 to 2025, 74 patients participated in the study. The median age was 62 years; 55 patients (74.3 %) were male and 19 (25.7 %) were female. The tumor was located in the upper third of the esophagus in 9 cases (12 %), the middle third in 31 cases (42 %), and the lower third in 34 cases (46 %). The ECOG performance status was 0 in 11 patients (14.9 %), 1 in 38 patients (51.3 %), and 2 in 25 subjects (33.8 %). The median OS was 13.6 months (95 % CI 10.6-NR), the median PFS was 9.7 months (95 % CI 7.1–22.0), the ORR was 55.4 % (95 % CI 44.1–66.2), and the disease control rate was 78.1 % (95 % CI 67.8–86.0). The most common grade 3–4 adverse events (AEs) during the study were leukopenia (11 cases, 14.8 %), neutropenia (12 cases, 16.2 %), anemia (10 cases, 13.5 %), and thrombocytopenia (15 cases, 20.2 %). There were no treatment-related deaths. Conclusions. The modified 2-week mDCF chemotherapy regimen demonstrated significant improvements in ORR, OS, and PFS, as well as manageable toxicity as a first-line treatment for esophageal squamous cell carcinoma.